What is the Role of Legal Systems in Financial Intermediation? Theory and Evidence - Laura Bottazzi; Marco Da Rin; Thomas Hellmann (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2007)
We develop a theory and empirical test of how the legal system affects the relationship between a venture investor and an entrepreneur. The theory uses a double moral hazard framework to show how optimal contracts and investor actions depend on the quality of the legal system. The empirical evidence is based on a sample of European venture capital deals. The main results are that with better legal protection, investors give more non-contractible support and demand more downside protection, and they develop more value-adding skills. These predictions are stongly supported by the empirical analysis. We also find that the investor's legal system is more important that of the company in determining these effects, and that legal system effects persist within civil law countries.
Keywords: 330; Finanzintermediation; Anlegerschutz; Risikokapital; Rechtsordnung; Schätzung; EU-Staaten